The Powerpoint Imagination: visualization and managerial vocabularies in sustainability reports - Ganesh, Shiv; Harness, Delaney; James, Samantha; Klingelhöfer, Julius; Schnell, Mackenzie; Palakshappa, Nitha (Journal of Environmental Planning and Management, 2023)
Sustainability reporting has been established as a dominant but problematic communication practice in global sustainability management. In this paper, we challenge the commonplace view of reporting as the simple and textual transmission of information, by interpreting corporate sustainability reports as visual artefacts that encourage particular views of environmental issues. We discuss visualization as a key practice in communication and rhetoric, asking what visual managerialism looks like in corporate reports, focusing on a corpus drawn from the Swedish United Nations Global Compact. We engage in a three-stage rhetorical critique to identify three kinds of visualizations: numerical, diagrammatic, and pictorial, establishing how they emphasize communicative characteristics such as logic, simplicity, and clarity. We consolidate these characteristics with the term ‘Powerpoint Imagination,’ arguing that they construct environmental problems in terms of a technocratic solutionism, i.e., efficiency, standardization and control. We discuss some issues with the Powerpoint Imagination by contrasting it with other images from sustainability reports, concluding with implications for future research.
CRIS-Team Scopus Importer:2023-12-01
Keywords: environmental reporting; images; managerialism; visual rhetoric; visualization